A Field Guide to the Poetry of Theodore Roethke - Hirsch, Edward; Barillas, William David (Book collections on Project MUSE., 2021)
"This volume is the first to reconsider Roethke's work in terms of the expanded critical approaches to literature that have emerged since his death in 1963. The forty-four contributors include highly respected literary scholars, critics, and writers, such as Peter Balakian, Camille Paglia, Jay Parini, and David Wojahn, who collectively make a case for Roethke's poetry as a complete, unified, and evolving body of work. The accessible essays employ a number of approaches, including formalism, ecocriticism, reader-response, and feminist critique to explicate the poetics, themes, and the biographical, historical, cultural, and literary contexts of Roethke's work"--